2006
DOI: 10.1128/jcm.44.2.536-546.2006
|View full text |Cite
|
Sign up to set email alerts
|

Use of PCR-Restriction Enzyme Pattern Analysis and Sequencing Database for hsp65 Gene-Based Identification of Nocardia Species

Abstract: Nocardia identification required laborious and time-consuming phenotypic and chemotaxonomic methods until molecular methods were developed in the mid-1990s. Here we reassessed the capacity of PCR-restriction enzyme pattern analysis (PRA) of the hsp65 gene to differentiate Nocardia species, including 36 new species. Our results confirm that hsp65 PRA must no longer be used for Nocardia species identification, as many species have the same restriction pattern. We then compared sequencing-based strategies using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 34 publications
3
120
0
5
Order By: Relevance
“…Thus, the use of PRA can lead to erroneous species identification of both clinical and environmental Nocardia isolates [19]. In our study, the pattern obtained by PCR-RFLP were confirmed by nucleotide sequence analysis of this fragment, which showed 100% homology with sequences of Nocardia asteroides retrieved from GenBank (ATCC no.…”
Section: Resultssupporting
confidence: 76%
“…Thus, the use of PRA can lead to erroneous species identification of both clinical and environmental Nocardia isolates [19]. In our study, the pattern obtained by PCR-RFLP were confirmed by nucleotide sequence analysis of this fragment, which showed 100% homology with sequences of Nocardia asteroides retrieved from GenBank (ATCC no.…”
Section: Resultssupporting
confidence: 76%
“…Currently, 16S rRNA gene sequencing is considered a better method for identification of Nocardia to the species level (Borriello et al, 2007), although certain isolates that have been found to have a high sequence similarity (99.8 %) from 16S rRNA sequences are recorded as distinct species by DNA-DNA hybridization (Conville et al, 2004;Rodríguez-Nava et al, 2006). McTaggart et al (2010) applied multilocus sequence analysis to 190 clinical isolates of Nocardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…As the hsp65 gene has more microheterogeneity regions compared with the 16S rRNA gene and is three to four times more discriminatory, this gene sequence has been targeted for Nocardia spp. identification (Rodríguez-Nava et al, 2006;Schlaberg et al, 2008;Yin et al, 2007). However, very few sequences of the hsp65 gene of Nocardia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction endonuclease analysis using portions of the 16S rRNA gene and the 65-kDa heat shock protein gene has been used in the past for the identification of commonly isolated Nocardia species (4,10). However, the usefulness of this procedure is becoming limited (8) due to the need to determine restriction fragment length polymorphisms (RFLPs) for the expanding number of described pathogenic species and the increasing number of restriction endonucleases required to make the species distinctions among these species. Therefore, sequence analysis of an alternative gene appears to be a viable adjunct to, or even a substitute for, 16S rRNA gene sequencing for the precise identification of Nocardia species.…”
mentioning
confidence: 99%